2020
DOI: 10.4103/ams.ams_107_20
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of palatal pleomorphic adenoma (PPA) recurrence after 10 years, treated at a Brazilian center - A case report

Abstract: Pleomorphic adenoma, considered the most frequent benign mixed neoplasm of the minor salivary glands, occurs mainly in the region of the hard palate, with slight predilection in females and peak of incidence between the third and fifth decades of life. An increase in recurrence rates has been associated with the histopathological variants of the tumor, cellular characteristics, stroma, and capsule rupture during surgical removal of the lesion. The present case report aims to describe the surgical approach perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The pseudocapsule is continuous in pleomorphic adenoma when it presents in the major salivary gland. However, when the tumor is present in the minor salivary gland, the pseudocapsule may be incomplete in some places [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pseudocapsule is continuous in pleomorphic adenoma when it presents in the major salivary gland. However, when the tumor is present in the minor salivary gland, the pseudocapsule may be incomplete in some places [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the risk of bias of cases reports of RPA included are available as supplementary data (see Data Availability Statement section). Six studies demonstrated low risk of bias 25,26,28,[30][31][32] , six studies demonstrated unclear risk of bias 21,23,24,27,29,33 , and one study demonstrated high risk of bias 22 .…”
Section: Risk Of Bias In Studiesmentioning
confidence: 98%
“…Thirteen articles met the eligibility criteria and were selected for full-text analysis. All 13 articles fulfilled the inclusion criteria and were included in this review: two retrospective studies 21,22 , 10 case reports [23][24][25][26][27][28][29][30][31][32] , and one letter to the editor 33 . All 13 studies were published in English, between 1957 and 2022, and were conducted in United Kingdom 24,25,33 , India 29,32 , United States 22,23 , Japan 21 , Greece 26 , Iran 27 , Italy 28 , South Africa 31 , and Brazil 30 .…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations